2020
DOI: 10.1002/cssc.201903108
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Effect of Trace Water on the Structure and Activity of NixCo1−x Electrocatalysts for the Methanol Oxidation Reaction

Abstract: Highly active Ni‐based catalysts have attracted much attention but are still facing challenges owing to the immature synthetic method. Herein, polyhedral NixCo1−x alloy was prepared by a facile modified polyol method in which a trace amount of water could halve the particle size of the alloy. The Ni/Co ratios in NixCo1−x alloy strictly depended on the used amount of water owing to the different solubilities of the precursors. Among them, the Ni0.6Co0.4 nanoparticles obtained with 70 μL of deionized water exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…However, Co 3 O 4 NP/NF not only showed a relatively large ECSA but also an obvious high specific activity converted from the ECSA, suggesting that there were a superior intrinsic activity and a strong ability to activate the methanol molecules and reduce the (CO) ads on the surface of the catalysts. 13,14,43,44 It is further demonstrated by CO-stripping voltammograms in Figure S11. For Co 3 O 4 NP/NF, the CO electro-oxidation peak appears at a more negative potential, which also shows the highest peak current density, indicating the preference of CO oxidative desorption.…”
Section: Resultsmentioning
confidence: 74%
“…However, Co 3 O 4 NP/NF not only showed a relatively large ECSA but also an obvious high specific activity converted from the ECSA, suggesting that there were a superior intrinsic activity and a strong ability to activate the methanol molecules and reduce the (CO) ads on the surface of the catalysts. 13,14,43,44 It is further demonstrated by CO-stripping voltammograms in Figure S11. For Co 3 O 4 NP/NF, the CO electro-oxidation peak appears at a more negative potential, which also shows the highest peak current density, indicating the preference of CO oxidative desorption.…”
Section: Resultsmentioning
confidence: 74%
“…However, despite their potential advantages, DAFCs generally have slow kinetics [223] . In addition, various intermediates such as CO, aldehyde could be strongly adsorbed on the electrode surface and poison the active sites of the Pt catalyst [224] . It is thus vital to develop materials with fast kinetics and high durability.…”
Section: Applications Of Bio‐templated Mnms For Different Electrocatamentioning
confidence: 99%
“…Pd‐based materials have been found to show higher activity than Pt‐based catalysts towards EOR in alkaline conditions [224,225] . Controllable synthesis of Pd NMs with well‐defined morphology and size is thus beneficial to construct anode material.…”
Section: Applications Of Bio‐templated Mnms For Different Electrocatamentioning
confidence: 99%
“…Compared with the monometallic catalyst, previous studies have shown that the bimetallic alloy Ni-based catalysts can improve the electrocatalytic activity for methanol oxidation reaction. [14][15][16][17][18] Li et al [19] synthesized the bimetallic NiSn nano-catalysts with 3-5 nm particle size by adjusting the Ni/Sn ratio. The electrochemical results showed that the interaction between Ni and Sn could improve the electrocatalytic activity for MOR.…”
Section: Introductionmentioning
confidence: 99%
“…As we all know, introduction the appropriate second metal or components can modify the electronic structures of the active metals and further improve the catalytic performance. Compared with the monometallic catalyst, previous studies have shown that the bimetallic alloy Ni‐based catalysts can improve the electrocatalytic activity for methanol oxidation reaction [14–18] . Li et al [19] .…”
Section: Introductionmentioning
confidence: 99%